A Study on the Performance of Exotic and Indigenous Chicken under Scavenging Method - Khan, ABMKI; Uddin, MB; Alam, J; Baset, MA (Journal of Science Foundation, 2013)
A study was conducted on the performance of exotic laying birds under scavenging systems at Sharishabari, Jamalpur during July, 2005 to June, 2006. For this purpose four exotic (three female and one male) and three local birds were provided to the six landless and six marginal cooperator farmers whereas six landless and six marginal non-cooperator farmers were considered as control. The average mortality in exotic chicken was 55% in case of local breed. The body and egg weight of exotic birds (1.65 kg and 56 gm respectively) were higher than the local breed (1.00 kg and 54 gm respectively). The average egg production per year was found to higher in exotic (84) than the local breed (62). But the benefit cost ration of exotic was found to be lower (1.36) than the local breed (1.46). DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14617 J. Sci. Foundation, 8(1&2): 31-34, June-December 2010